2012
DOI: 10.1002/bdrb.21004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity Evaluations of Whole Mixtures of Disinfection By‐products using Concentrated Drinking Water in Rats: Gestational and Lactational Effects of Sulfate and Sodium

Abstract: A developmental toxicity bioassay was used in three experiments to evaluate water concentrates for suitability in multigenerational studies. First, chlorinated water was concentrated 135-fold by reverse osmosis; select lost disinfection by-products were spiked back. Concentrate was provided as drinking water to Sprague-Dawley and F344 rats from gestation day 6 to postnatal day 6. Maternal serum levels of luteinizing hormone on gestation day 10 were unaffected by treatment for both strains. Treated dams had inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Concentrations of each component DBP are listed in Table 1 . Chemical proportions were based on those reported at the water utility that provided water for our whole-mixture toxicity studies ( Narotsky et al 2012 , 2013 ); these proportions were held constant across dose levels (0, 500×, 1,000×, or 2,000× of the MCLs). Overall dose levels were selected based on results of a preliminary dose-range–finding study with pregnant and lactating rats.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of each component DBP are listed in Table 1 . Chemical proportions were based on those reported at the water utility that provided water for our whole-mixture toxicity studies ( Narotsky et al 2012 , 2013 ); these proportions were held constant across dose levels (0, 500×, 1,000×, or 2,000× of the MCLs). Overall dose levels were selected based on results of a preliminary dose-range–finding study with pregnant and lactating rats.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the potential toxicity of whole DBP mixtures at environmentally relevant doses, including unidentified DBPs, we conducted a reproductive study where water was concentrated 136-fold, chlorinated, and provided as drinking water to rats through the production of two generations of progeny. Because this was an entirely new approach to the toxicological study of drinking water, substantial efforts were made to (1) create a new method for concentrating and disinfecting whole drinking water mixtures (to retain DBPs lost by other methods), (2) maintain a water matrix suitable for in vivo and in vitro testing, (3) create a specialized water delivery system, (4) optimize experimental designs to increase our ability to detect subtle effects, and (5) improve analytical methods to measure DBPs in water concentrates. Because of the low exposure levels, the experimental design was optimized to provide enhanced statistical power relative to that which would have been provided by conventional study designs, particularly for developmental end points of pup weight and prenatal loss, which were of particular importance given epidemiological data. In addition to developmental and reproductive end points, we examined immunological and neurobehavioral end points.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on the toxicity endpoints of genotoxicity, carcinogenicity, and reproductive effects related to health effects (Villanueva et al 2015). The toxicities of several mixtures of disinfection by-products in rats have been investigated, and pregnancy loss and eye malformations have been detected in rat offspring after gestational exposure to mixtures of regulated disinfection by-products; male rats significantly increase the incidence of retained nipples and impaired sperm motility (Narotsky et al 2008(Narotsky et al , 2011(Narotsky et al , 2012(Narotsky et al , 2015Konkel 2015). In addition, a comprehensive study has indicated that disinfection by-product mixtures have implications for the potential developmental, reproductive, or carcinogenic health of humans (Simmons et al 2008).…”
Section: Introductionmentioning
confidence: 99%